KASUS INFEKSI IRIDOVIRUS PADA BENIH IKAN KERAPU PASIR, Epinephelus corallicola DI HATCHERY - Fris Johnny; Des Roza (Universitas Gadjah Mada, 2009)
Seeding effort of coral grouper fish, Epinephelus corallicola in Research Institute for Mariculture (RIM) Gondol, Bali has been blazed the way, but rearing seed still found constraint as height of mortality. One of death cause of seed is by virus infection disease. An attempt for diagnosis iridovirus infection at seed coral grouper Fish age sand around 60 days shows symptom as no eating, populating in basin base, colour turn darken, and here in after death. Disease detection of the showing symptom seed that has not generated death is observed based on pathological anatomy and viral detection with PCR-probe. Disease detection also conducted to seed after showing symptom and generated high death. Detection based on pathological anatomy result many